Idiopathic gingival fibromatosis - Nitin Hemchandra Dani; Dinkar Parveen Khanna; Vaibhavi Hitesh Bhatt; Chaitanya Pradeep Joshi (Wolters Kluwer Medknow Publications, 2015)
Idiopathic gingival fibromatosis (IGF) is a rare hereditary condition characterized by slowly progressive, nonhemorrhagic, fibrous enlargement of maxillary and mandibular keratinized gingiva caused by increase in submucosal connective tissue elements, mostly associated with some syndrome. This case report describes a case of nonsyndromic generalized IGF in an 18-year-old male patient who presented with generalized gingival enlargement. The enlarged tissue was surgically removed by internal bevel gingivectomy and ledge and wedge procedure. The patient was regularly monitored clinically for improvement in his periodontal condition as well as for any recurrence of gingival overgrowth.